Comprative Analysis of 4G Network Quality Between Telkomsel and Indosat Operators Using the G-Net Track Pro Application in the City of Ternate - Irwan Abdullah; Zulaeha Mabud; Fahrizal Djohar; Fedi Haryanto H Tjan (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
In some areas the distribution of telecommunications networks is not evenly distributed, one example is in the city of Ternate. Several areas in the city of Ternate. The purpose of this study is to determine the quality of the 4G LTE network from providers in the city of Ternate, namely (Telkomsel and Indosat) using the G-Nettrack Pro application, the parameters measured are rsrp or network strength, The method used in this study is the drive test, The results showed that the RSRP distribution of Telkomsel operators in Sasa Village had a percentage of 43.05% with a sample of 155. Meanwhile, Indosat operators had a percentage of 34.83% with a sample of 117, the RSRP distribution of Telkomsel operators in Gambesi Village had a percentage of 42.02% with a sample of 133. While Indosat Operators have a percentage of 24.64% with a sample of 70, RSRP Distribution of Telkomsel Operators in the Stadium Village has a percentage of 64.29% with a sample of 117. Meanwhile, Indosat Operators have a percentage of 53.05% with a sample of 87, Distribution of RSRP Telkomsel Operators in Kelurahan Stadiums have a percentage of 57.76% with a sample of 145. Meanwhile, Indosat Operators have a percentage of 37.18% with a sample of 87.